The Effect of Extension Through the Pilot Method of Seeding Rice Seeds Using Youtube Media on Increasing Farmers' Skills in Seeding Rice Seeds - Muhamad Ilham; Jamaris Jamna (Universitas Negeri Padang, 2021)
Extension is the dissemination of information to farmers and is a non-formal education so that farmers recognize a farm and can solve problems properly and correctly. Extension techniques are important to be reached by every extension so that the counseling carried out can be accepted and reached by the learning community. This study was conducted to determine the effect of counseling on sowing rice seeds with a pilot method using YouTube media on improving farmers' skills in sowing rice seeds in the Buik Caliak Indah farmer group. The type of research applied is quantitative research. While the method used is the experimental method. The experimental design applied by Pre Experimental Design in the form of using one group Pre Test-Post Test. The instrument that the researcher used in this study was a test of the Pre Test-Post Test section. The data analysis technique in this research is hypothesis testing using the t-test formula. The population is group members who are in the Bukik Caliak Indah Nagari Campago Farmer Group, District V Koto Kampung Dalam, Padang Pariaman Regency, collecting 40 people while the sample is 50% of the population. Based on the results of the Pre Test study the average value of knowledge was 52.25, after the Post Test 92.75. While the average value of Pre Test skills was 53.0, after Post Test was 87.5 and there was a significant effect between counseling through the pilot method of using YouTube media to increase farmers' skills in sowing rice seeds.